ANALISIS PENGARUH VARIABEL PENGAUDITAN DAN VARIABEL KEUANGAN TERHADAP OPINI AUDIT GOING CONCERN - Lim, Alex Christian; Stephanus, Daniel Sugama (Parsimonia - Jurnal Ekonomi dan Bisnis, 2023)
ABSTRACT This study aims to prove the influence of these variables on going concern audit opinions. these variables consist of two factors, namely auditing factors and financial factors. The auditing factors used in this study consist of audit quality, auditor reputation, audit tenure, audit lag, and opinion shopping. Then, the financial factors used in this study consist of profitability, liquidity, solvency, and leverage. The sample used in this research is a manufacturing company in the consumer goods industry sector which is listed on the Indonesia Stock Exchange. The sample selection was carried out using a purposive sampling technique. Based on the sample selection process, 33 sample companies were obtained and the research observation period was carried out for 5 years, so that the total was 165 data, from 33 manufacturing companies in the consumer goods industry sector for 5 years. The type of data used is secondary data published by the Indonesia Stock Exchange, in the form of audited financial report data along with reports from independent auditors of manufacturing companies in the consumer goods industry sector. Data collection techniques were carried out using documentation techniques by searching for and collecting research object data. The analysis in this study uses logistic regression. The results of this study indicate that all independent variables used in this study have no significant effect on going concern audit opinion. This is because in this study using a sample of companies that do not experience negative profits (losses). Therefore the result is that all the independent variables used in this study have no significant effect on giving a going-concern audit opinion to companies that experience positive net profit (profit). Keywords: Going Concern Audit Opinion, Audit Quality, Auditor Reputation, Audit Tenure, Audit Lag, Opinion Shopping, Profitability, Liquidity, Solvency, Leverage.